Tuning the electronic state of metal/graphene catalysts for the control of catalytic activity via N- and B-doping into graphene. Issue 52 (8th June 2018) - Yun, Yang Sik; Park, Hongseok; Yun, Danim; Song, Chyan Kyung; Kim, Tae Yong; Lee, Kyung Rok; Kim, Younhwa; Han, Jeong Woo; Yi, Jongheop
Abstract : Catalytic activity was efficiently tuned via manipulating the electronic state of a catalyst, induced by a facile doping method in a metal/graphene system. Abstract : Catalytic activity was efficiently tuned via manipulating the electronic state of a catalyst, induced by a facile doping method in a metal/graphene system. The strategy was proven to be applicable to not only transition metal but also noble metal catalysts in CO hydrogenation and 4-nitrophenol reduction.